Efektivitas Penerapan Model Project Based Learning Pada Mata Pelajaran Desain Grafis Percetakan Kelas XI Di SMKN 2 Kecamatan Guguak - Giska Widi Tisara; Fetri Yeni J; Syafril Syafril; Zuliarni Zuliarni (Departement of Mathematics Education, 2023)
Based on observation researcher did about Graphic Design Printing at SMK N 2 Guguak, many students do not follow the lessons well. Students easily get bored paying attention to the teacher's explanation. One of the factors that causes this is monotonous learning. This studies goals to test the effectiveness of applying the project based learning in improving the output of the students in XI Multimedia at SMK N 2 Guguak in the subject of graphic design printing. This research technique is a quantitative quasi-experiment with a post-test only design. The specimen in this studies are 49 students. The instrument is a multiple choice questions consisting 20 items. The research data was processed using descriptive and inferential analysis techniques. The results of this research discovered that the average of student’s outcomes in the experimental class using Project Based Learning is better than student’s outcomes in the control class that used conventional learning. Based on the speculation, it could be concluded that the applying of the project based learning is effective in enhancing students output in class XI Multimedia at SMK N 2 Guguak in the subject of graphic design printing.